HUBUNGAN PENGETAHUAN BUSANA DENGAN PENAMPILAN BERBUSANA KE KAMPUS MAHASISWA TATA BUSANA JURUSAN KESEJAHTERAAN KELUARGA FT UNP - fajria, salmi; katin, yusmar emmy; rahmiati, rahmiati (Journal of Home Economics and Tourism, 2013)
Abstract This problems were about presentation in fashion go to thecampus of students Tata Busana Jurusan KesejahteraanKeluarga FT UNP. The purpose of this research to saw thecorelation between knowledge with presentation in fashion go tothe campus of students Tata Busana Jurusan KesejahteraanKeluarga FT UNP in 2009 and 2010. The form of this researchwas descriptive corelation means the research that given theilustration about the corelations between fashion know ledgevariable (X) with fashion presentation variable (Y). Thepopulation and sample in this research were the students of TataBusana 2009 and 2010 were consist of 65 persons. To choosethe sample by using total sampling technique. The researchinstrument was test method and questionnaire with likert scale.The data analize used descriptive statistic and corelationanalysis technique used Test t. The result of this research got (1)fashion knowledge variable in poor category (32,3%), (2) thefashion presentation go to the campus in fair category (47,7%),and (3) The writer got the positive corelation between fashionknowledge (X) with fashion Presentation go to the campus (Y)of the students Tata Busana Jurusan Kesejahteraan Keluargawith contribution (23,9%).Â  Â Kata Kunci: Pengetahuan, Penampilan, Berbusana ke Kampus